(untitled) (International Journal of Emerging Trends in Science and Technology, 2017)
-In this paper, Some results on Strongly pseudo Irregular Fuzzy Graphs and Strongly pseudo total Irregular Fuzzy Graphs are established. Comparative study between Strongly pseudo Irregular Fuzzy Graphs and Strongly pseudo total Irregular Fuzzy Graphs is done. Also defined  - pseudo domination set and  -pseudo total dominating set in irregular fuzzy graph.